Perancangan Robot Light Follower untuk Kursi Otomatis dengan Menggunakan Mikrokontroler ATmega 328P - Roslidar Roslidar; Alfatirta Mufti; Haris Akbarsyah (Jurnal Rekayasa Elektrika, 2017)
This article discusses the design of light follower chair prototype with speed adjustment of DC motor according to light intensity using microcontroller ATmega328p. This prototype provides a solution for a chair to be back on the position under the table automatically by using a light follower robot principle. There are many possible positions of a chair after being used: perpendicular or sideways to the table. As the positions after being used are varied, the light is used to direct the chair toward under the table since the light can reach the area around the chair except for the back area. This prototype functions well if the chair is heading to the table and is not designed to function in the backward position. LDR (Light Dependent Resistor) sensors are used to detect the light. As the source of light, 1 W high power LED is put under the table. A microcontroller ATmega328p is used to execute the input and output of this system. Two DC motor are used as actuators to control the movement of the chair toward the light under the table. Ultrasonic sensors HC-SR04 are used to measure the distance between the table and the chair so that the chair can stop at the desired position.